Thy1-YFP: an effective tool for single cell tracing from neuronal progenitors to mature functionally active neurons - Ante Plećaš; Katarina Kapuralin; Leonarda Grandverger; Dinko Mitrečić; Ivan Alić (Cell Death Discovery)
Abstract The differentiation of mouse neurons is a complex process involving cell maturation and branching, occurring during both, embryonic development and differentiation in vitro. To study mouse neuronal morphology, we used the Thy1 YFP-16 mouse strain. Although this mouse strain was described over twenty years ago, detailed studies on projections outgrowth and morphology of neurons are still lacking. The main goal of our study was to analyse the differentiation patterns of neural stem cells, including markers of differentiation, colocalization patterns, synaptic markers and the tracing of cell projections during differentiation in vitro. The neural stem cells were isolated from embryos at embryonic day 14.5 as well as newborn pups and differentiated into neurons and astrocytes. Our data showed a significant decrease of neural stem cells markers and a substantial increase in neuronal markers during differentiation, analysed by immunocytochemistry, quantitative PCR and western blot. To assess synaptic maturation, neurons were further analysed by quantitative PCR and immunocytochemistry. Expression of synaptic markers were increased during differentiation in vitro. At the 7th day in vitro differentiation, expression of synaptic markers in both YFP positive and YFP negative neurons were at comparable levels. Finally, our data revealed a significant increase in all measured morphological parameters: Filament Area, Filament Length, Filament No. Terminal Points and Sholl Intersections in YFP positive/MAP2 positive neurons compared to YFP negative/MAP2 positive neurons. These findings suggest that YFP is an effective tool for cell tracing both in vivo and in vitro, making it valuable for morphological studies during development as well as in the context of neurodegenerative disorders.